Raman spectroscopy as a reliable tool for strain analysis in iii-nitride superlattices - Maia de Oliveira, Fernando (2021)
Since its discovery, the Raman effect has been a great ally in the structural investigation of a wide variety of materials, from macro to nanoscale. However, despite the remarkable sensitivity of techniques based on Raman shift in detecting features associated to atomic vibrations, a limit of accuracy in results is imposed by the imprecision in determining the parameters associated to the traditional method of interpretation of Raman shift. In this formulation, a linear association is considered between strain and Raman shift, which dependency is defined by a set of deformation potentials and elastic constants that have specific values for the material in analysis, depending for instance on its crystalline symmetry. This doctoral thesis presents an alternative method for performing more accurately strain analysis of nanostructures using Raman shift. To do so, a set of six -period were fabricated using plasma-assisted molecular beam epitaxy, defining different thickness of among distinct samples. The superlattices were analyzed by x-ray diffraction, displaying a distribution of in-plane tensile and compressive strain. By using optical microscopy, a mosaic of cracks was observed promoting the reduction of tensile strain in parts of the structure. The Raman shift was acquired in different positions of each superlattice, and then used to calibrate a nonlinear correlation model based on the phenomenon of lattice coherence with results from x-ray diffraction. Using the nonlinear model, the technique of micro-Raman was employed to perform one- and two-dimensional strain mappings of the superlattices, evidencing the distribution of values of strain around the lines of structural cracks. A strain dependence with the distance to cracks was also verified, exhibiting an approximately constant value of residual strain after a few micrometers apart from any line of crack. The maximum and minimum values of in-plane tensile strain in the layers of and in-plane compressive strain in the layers of are also dependent on the thickness of employed in each superlattice. This alternative interpretation of Raman shift allows not only the acquisition of more precise values of strain for nitrides superlattices, but it also shows applicability for a wide range of heterostructures in nanoscale.